2019
DOI: 10.2147/ppa.s222181
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patients’ Perceptions To Reduced Orthodontic Treatment Time In Saudi Arabia</p>

Abstract: PurposeTo evaluate patients’ perceptions regarding orthodontic treatment duration, cost, and willingness to undergo different procedures and techniques available to accelerate orthodontic tooth movement in Saudi Arabia.Patients and methodsA cross-sectional survey was conducted in Saudi Arabia from January to March 2019. Patients from multiple centers were electronically surveyed regarding their perception of orthodontic treatment duration, acceptance of appliances and techniques available to shorten the durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 17 publications
4
15
0
1
Order By: Relevance
“… 2 Linjawi et al, also found that females and patients aged between 18-25 years old were more interested in orthodontic treatment. 24 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 2 Linjawi et al, also found that females and patients aged between 18-25 years old were more interested in orthodontic treatment. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also reported by Linjawi et al, although they had a broader age group and gender distribution. 24 Likewise, one-third of the adult patients interviewed by Uribe and others suggested that orthodontic treatment took longer duration and more than half of them wished that orthodontic treatment could last for 12 months or less. On the other hand, adolescent patients preferred shorter period of orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations